Statistical evaluation of morphological parameters of porous nanostructures on the synthesized indium phosphide surface - Kosach, N.I.; Bolshakov, V.B.; Bohdanov, I.T.; Suchikova, Y.O. (KU Publ., 2021)
A constructive method for estimating the surface morphology of nanostructured semiconductors, which consists in determining the main statistical characteristics of the aggregate structure of nanoscale objects on their synthesized surface is presented. In terms of the indium phosphide semiconductor with a synthesized porous layer on its surface, it is shown that the evaluation of the main statistical characteristics allows a deeper understanding of the kinetics of the pore formation process during typical electrochemical treatment of the crystal. The determination of the main statistical metrologically based characteristics (indicators of the distribution center, variation, and shape of the distribution) allows us to understand in more detail view the processes occurring during electrochemical processing of crystals. In the long run, this will make it possible to create nanostructures with predetermined properties, which will become the basis for the industrial production of high-quality nanostructured semiconductors.
Индий фосфидінің синтезделген бетіндегі кеуекті наноқұрылымдардың морфологиялық параметрлерін статистикалық бағалау
Статистическая оценка морфологических показателей пористых наноструктур на синтезированной поверхности фосфида индия
Keywords: synthesis; semiconductors; surface morphology; measurement; aggregate structure; statistical analysis; indium phosphide; ImageJ